25 Tender Is the Spine: Thoracolumbar Fractures and Patterns of Referrals. (28th February 2022) - Saad, A.R.; Mueller, M.; Pillai, D.
Abstract: Introduction: This study investigates the pattern of referrals of thoracolumbar fractures between trauma and orthopaedic department in a district general trauma unit (TU) and the affiliated Major Trauma Centre (MTC). Our TU has got no out of hour emergency spinal surgeons on site. Patients who are admitted with thoracolumbar fractures get referred to MTC for advice on management. The TLICS score and the AO Thoracolumbar fracture classification system are two well recognized classification systems for thoracolumbar fractures. The main aim of this project is to evaluate current practice and its effectiveness. Method: Data was retrospectively collected from the trauma board for patients referred to the orthopaedic on call services for thoracolumbar fractures over a 16-month period. Patients' demographics, mechanism of injury, TLICS scores and AO classification were recorded, and outcome registered. Results: From 92 patients identified most had low energy trauma and the majority had low TLICS score (<2) and AO class (A1, 2, 3). 24 of the patients were referred to MTC of whom 10 required a follow-up appointment. 39 were discussed with the local spinal consultants. 91 were treated conservatively and locally. Conclusions: Most thoracolumbar fractures are treated locally. It can be argued that the emergency spinal services at MTC are unnecessarily burdened for advice and reassurance. A change of the current pathway can possibly be put in place for patients with low AO classification (A1, 2, 3), that can be treated with local spinal surgeon input. This calls for a follow-on multi-centre study.